PERAN PENANDA MOLEKULER PADA TERAPI GLIOMA - Rusdy Ghazali Malueka,* Yudiyanta,* Ahmad Asmedi* (Neurona Majalah Kedokteran Neuro Sains, 2017)
GLIOMAS ARE THE MOST COMMON PRIMARY CENTRAL NERVOUUS SYSTEM CNS TUMORS IN ADULTS NOWDAYS GLIOMA CLASSIFICATION HAS BEEN CHANGED FROM MORPHOLOGICAL BASED TO MOLECULAR BASED CLASSIFICATION